A Delay from Diagnosis to Treatment Is Associated with a Decreased Overall Survival for Patients with Endometrial Cancer - Dolly, Darren; Mihai, Andreea; Rimel, B. J.; Fogg, Louis; Rotmensch, Jacob; Guirguis, Alfred; Yordan, Edgardo; Dewdney, Summer (Frontiers in Oncology, 2016)
OBJECTIVES: While Caucasian women are more likely to be diagnosed with endometrial cancer compared to African Americans women, the rate of mortality is higher for African Americans. The cause of this disparity is unknown. We analyzed the time interval from diagnosis of endometrial cancer to treatment as it pertains to race and socio-economic factors, and its possible impact on survival. METHODS: This was a retrospective, single institution chart review using a cancer registry database. We identified 889 patients who were diagnosed with endometrial cancer between January 2005 to June 2012. Clinicopathologic characteristics, demographics, insurance status, distance from medical center, BMI, dates of diagnosis, and treatment were obtained from the medical records. Survival and association was determined by a one-way ANOVA test. RESULTS: At the time of the study 699 patients were alive and 190 dead. The average age was noted to be 62 years (24-91years). Stage I, II, III and IV disease accounted for 69%, 6%, 15%, and 10% respectively. White race accounted for 64%, African Americans 24% and Hispanics 7% of our study population. Majority of patients were privately insured (n=441) followed by Medicare (n=375). The mean interval time from diagnosis to treatment was 47.5 days (0-363). A statistically significant difference was noted for this time interval with regard to both race and insurance status; white and African Americans (42.6 vs. 57.3 days, p 0.048), privately insured and Medicare (38.4 vs. 54.1days, p<0.001). There was a significant association with increased risk of death with a longer delay (43.3 vs. 64.8 days, p <0.001). No statistically significance was noted for distance from medical center or BMI. CONCLUSION: A significant increase in interval of time from diagnosis to treatment of endometrial cancer was seen in both race and insurance status. A longer interval from diagnosis to treatment was associated mortality. The causes of these delays are likely multifactorialbut deem further investigation given these data.